2013
DOI: 10.1007/s00167-013-2726-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term biomechanical outcomes after Achilles tendon ruptures

Abstract: Clinical scores do not predict biomechanical outcomes. Clinically measured MCC is a good predictor of PPFT and POFF and can easily be used in clinical practice. Relative POFF in side comparison as well as per body weight favours surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 40 publications
(84 reference statements)
3
42
3
2
Order By: Relevance
“…Though the type of treatment was limited to only one type of surgery, it is likely that these results are indicative of other surgical and conservative treatments. Previous work has shown that long-term biomechanical outcomes after ATR appear to be similar when comparing nonoperative treatments, open, and percutaneous surgeries (Rosso et al, 2013). Within this study intra-patient ratios of AT length were compared Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Though the type of treatment was limited to only one type of surgery, it is likely that these results are indicative of other surgical and conservative treatments. Previous work has shown that long-term biomechanical outcomes after ATR appear to be similar when comparing nonoperative treatments, open, and percutaneous surgeries (Rosso et al, 2013). Within this study intra-patient ratios of AT length were compared Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The rehabilitation of ruptured Achilles tendons includes varying loading programs, albeit without a real consensus with regards to the magnitude and when to initiate the loading . Intriguingly, despite extensive rehabilitation efforts, muscle weakness can persist for a considerable time after surgery and may even persist decade later . This muscle weakness has been attributed to a reduction in muscle cross‐sectional area (CSA), and the persistent muscle atrophy has prompted an emphasis on early mobilization following the repair of the ruptured tendon .…”
Section: Introductionmentioning
confidence: 99%
“…Tendons and ligaments are collagenous fibrous tissues, which connect bones and muscles, and transmit mechanical forces efficiently . Tendon and ligament injuries are treated surgically or non‐surgically, and both methods yielded overall good recovery rates . However, repaired tendon tissues are often histologically unorganized and usually have inferior mechanical strength, which can lead to re‐rupture .…”
mentioning
confidence: 99%